Essential C# 4.0, 3rd Edition - Michaelis, Mark (Addison-Wesley Professional, 2011)
Essential C# 4.0 is a well-organized,“no-fluff” guide to all versions of C# for programmers at all levels of C# experience. This fully updated edition shows how to make the most of C# 4.0’s new features and programming patterns to write code that is simple, yet powerful.